Perbedaan Efektifitas Metode Ceramah dan Media Video dalam Meningkatkan Pengetahuan Pembelajaran Praktikum Keperawatan - Agus Sustiyono (Faletehan Health Journal, 2021)
Among learning technologies, video has more advantages. Video play can describe an object or a process correctly and present taught skills repeatedly. Video is able to manipulate time and space and can invite participants to see various sizes of object and events anywhere. This study aims to determine the effects of video to increase the knowledge of first level students at Diploma III Nursing Study Program of Faletehan University Serang in nursing practices. The design of this research is quasi experimental with non-equivalent two groups design. The research samples were 96 first level students at Diploma III Nursing Study Program, which were divided into 2 groups. Group 1 received lecture treatment as many as 48 students and group 2 received video treatment as many as 48 students. The results showed the increase of knowledge mean score as much as 0.29 in the lecture treatment group and 2.21 in the video treatment group. The results also showed a significant difference of knowledge (p = 0.000). To conclude, there is a difference in the effectiveness of learning between lecture method and video-use on student knowledge in nursing practice.